Evaluation of the sulfate resistance of concrete with local fly ash - Legaspi, Jesusito B. Jr.; Diola, Nathaniel B. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
As an archipelagic, agricultural country, it is not uncommon for structures to be near bodies of water or agricultural lands. This type of construction may be vulnerable to sulfate attack. Type II Portland Cement is specified by design professionals for construction projects vulnerable to sulfate attack. However, Type II Portland Cement is not always readily available. As such, contractors use fly ash blended cement as a substitute. This research aims to provide locally relevant data with regard to the soundness of using fly ash blended cement in place of Type II Portland Cement. This will be accomplished by comparing the expansion and the strength loss of different fly ash - portland cement compositions subjected to sulfate attack.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Fly ash; Sulfate-resistant concrete